Analysis of Dyeing Process Quality at PT XYZ - Rahayu, Hestiani; Yun, Yun (International Journal of Education, Management, and Technology, 2025)
This study investigates the root causes of the "inconsistent color" defect in the dyeing process at PT XYZ and evaluates the effectiveness of corrective actions undertaken to address the issue. Pareto analysis revealed that inconsistent color accounted for over 50% of total production defects, indicating it as a critical quality concern. Root cause analysis using the Fishbone diagram and 5 Why method identified human and method-related factors as primary contributors, particularly inaccurate dye mixing due to uncalibrated measurement tools and the absence of standard operating procedures (SOPs). To address these issues, corrective actions were implemented using the Plan-Do-Check-Act (PDCA) cycle, including the development of SOPs, the introduction of quality control checklists, and targeted operator training. Following implementation, the defect rate decreased by 22.6% over a six-month period, demonstrating the effectiveness of structured quality improvement methods. While the study confirms the value of systematic interventions in enhancing product consistency, it is limited by its focus on a single defect type and a short observation period. Future research should investigate a broader range of defects and consider the integration of advanced quality management frameworks such as Six Sigma or Total Quality Management (TQM). The findings underscore the critical role of continuous process control, regular calibration, and workforce competence in achieving and sustaining high-quality standards in textile manufacturing.